If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 + -4x = x + -10 Reorder the terms: 35 + -4x = -10 + x Solving 35 + -4x = -10 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 35 + -4x + -1x = -10 + x + -1x Combine like terms: -4x + -1x = -5x 35 + -5x = -10 + x + -1x Combine like terms: x + -1x = 0 35 + -5x = -10 + 0 35 + -5x = -10 Add '-35' to each side of the equation. 35 + -35 + -5x = -10 + -35 Combine like terms: 35 + -35 = 0 0 + -5x = -10 + -35 -5x = -10 + -35 Combine like terms: -10 + -35 = -45 -5x = -45 Divide each side by '-5'. x = 9 Simplifying x = 9
| -11x^3+99x^2-154x=0 | | 8r+4=102r | | 0.95x+.05x(18-x)=.10(27) | | 4x^2-17x+9=-4x+6 | | 6x-8y=-56 | | x^2+10x-39=5x-3 | | 4x^2-11x+11=2x+2 | | -1-n=-(3n+3) | | 7=1+2 | | 4x^3+9x^2=-2x | | 3y-1+y+45=7y+50-5y | | 8x+2x+4=7 | | S(s+7)=18 | | 4m^2=5m-1 | | fx=5-2(-1) | | 5x^2=27x+56 | | -2(n-1)+3=-3+2n | | p+3=2-2(1+P) | | 3(3x+5)=2(6x+3) | | 12t+4(1-5t)= | | 7x-4=51 | | 11x^2+12x-8=0 | | A+14=20-a | | 4x-13x+12x= | | 5(3x+8)=-2(-5+6) | | 14x=7x+7 | | 28+2x=5x+1 | | -4(3x-8)=40 | | M+4=16 | | 33-3x=6x+17 | | 4x+9=3x | | a*6= |